Mental health burden and quality of life in elderly patients with chronic illnesses: A cross-sectional study in Southern India - Sidhartha Bharathy; Karthikeyan Rajamanickam; Bharathy Sundar; Reshma Ravi Nair (Asian Journal of Medical Sciences, 2025)
Background: Chronic medical conditions and depression frequently co-occur in elderly populations, yet their combined impact on quality of life (QoL) remains understudied in developing countries.